Dynamic thiol/disulfide homeostasis in children with community‐acquired pneumonia. Issue 3 (22nd February 2019) - Temel, Münevver Tugba; Demiryürek, Seniz; Temel, Levent; Saracaloglu, Ahmet; Eke, Necmi; Baysalman, Elif; Mammadov, Azad; Coskun, Mehmet E; Demiryürek, Abdullah T
Abstract: Background: Alteration in thiol level under oxidative stress may contribute to community‐acquired pneumonia (CAP). The goal of this study was to determine whether there are changes in thiol/disulfide homeostasis and nitric oxide (NO) in children with CAP. Methods: In total, 130 participants were involved in the study. Of these, 65 had been diagnosed with CAP on admission, and the remaining 65 were healthy individuals. Serum total thiol and native thiol were measured in each participant using a novel automated spectrophotometric method. The amount of dynamic disulfide bonds and related ratios were calculated from these values. Serum NO was measured on chemiluminescence assay. Results: Average native thiol, total thiol, and disulfide in the CAP group were significantly lower than in the healthy individuals ( P  <   0.0001, P  <   0.0001, P  =   0.0126, respectively). In addition, disulfide/native thiol ( P  =   0.0002), and disulfide/total thiol ratios ( P  =   0.0004) were significantly higher, whereas the native thiol/total thiol ratio ( P  =   0.0004) was lower in the CAP group. High serum NO was noted in the CAP group ( P  =   0.0003), but there was no marked correlation between thiol/disulfide and NO. Conclusion: The changes in endogenous thiol levels under oxidative stress may be associated with the pathogenesis of CAP in pediatric patients.